Hidden in plain sight? The human resource management practitioner's role in dealing with workplace conflict as a source of organisational–professional power. (27th July 2020) - Roper, Ian; Higgins, Paul
Abstract: This article examines the perceived importance of human resource (HR) practitioners' role as 'organisational professionals' at national and organisational levels. Informed by institutionalist theory and drawing upon interviews at national and organisational levels, a dissonance is identified in the degree to where HR's non‐substitutable expertise lies. It is concluded that HR's role in dealing with workplace conflict is under‐recognised at national level as it does not fit with the proactive 'strategic' narrative seen to be what HR needs to achieve to be influential. At organisational level, however, conflict management is a source of power because, unlike many other HR roles—valued as they may be—conflict management is the role that can least be substituted by non‐specialist HR practitioners because of its unpredictability.